In situ Growth Rate Assessment of the Hexactinellid Sponge Asconema setubalense Using 3D Photogrammetric Reconstruction - Prado, Elena; Cristobo, Javier; Rodríguez-Basalo, Augusto; Ríos, Pilar; Rodríguez-Cabello, Cristina; Sánchez, Francisco (Frontiers in Marine Science, 2021)
We describe for the first time the growth rate of Asconema setubalense (Porifera, Hexactinellida) through the use of a 3D photogrammetric methodology in a non-invasive and novel approach. Structure-from-Motion (SfM) techniques from videos acquired in different dates along 6 years with ROTV, Politolana in El Cachucho MPA (Cantabrian Sea) have been used. The cruises have been carried out in years 2014, 2017 and 2019. With these data a multi-temporal study has been proposed in the framework of MPA monitoring. A complete 3D reconstruction of the deep-sea floor for each date with Pix4D Mapper Pro software has been achieved. Having 3D point clouds of the study area allows us to propose a series of measures that were impossible to obtain in 2D images. So in this 3D space the sizes (height, diameter, cup-perimeter and cup-surface area) of several A. setubalense specimens have been measured for each year. The annual growth rates registered go from cero (“no growth”) for a large size specimen, to average of 2.2 cm.yr-1in cup-diameter, and 2.5 cm.yr-1in height for developing specimens. Growth curve using a von Bertalanffy model equation has been achieved. Taking into account the size indicators used in this study and based on von Bertalanffy growth model, this sponges reaches almost maximum size over 60 years of age, with a very low variation from there (< 0.5 cm.year-1). This growth rate of the Asconema setubalense has been successfully obtained through this study in the central Cantabrian Sea. During the monitoring program in the MPA a high number of specimens disappeared. This, raises suspicions of some phenomenon that is affecting the survival of this species in the area. This type of methodology based on images does not cause damage or alterations on benthic communities and it is particularly necessary in vulnerable ecosystem studies and MPA monitoring.